Pengaruh Partisipasi Anggaran, Evaluasi Anggaran dan Kejelasan Tujuan Anggaran Dana Desa terdapat KinerjaAparatur Pengelolaan Dana Desa (Studi di Kecamatan Nisam Antara) - Mulia Andirfa; Miswar; Faisal Faisal; Zuhra Izzati; Najwa Yusuf (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to examine budget participation, budget evaluation and the clarity of village fund budget objectives on the performance of village fund management officials in Nisam Antara District. The research location was in Nisam Antara District which consisted of Gampong Alue Papeun, Gampong Blang Jrat, Gampong Alue Dua, Gampong Darussalam Gampong Blang Pohroh, and Gampong Seumirah. The data used in this study are primary data with a sample of 79 people. Data processing is carried out with the help of multiple linear regression equation models. The results showed that: Partially budget participation, evaluation of the village fund budget and clarity of village fund budget objectives have positive and a significant effect on the performance of village fund management officials in Nisam Antara District. Simultaneously budget participation, budget evaluation, and clarity of village fund budget objectives have a significant effect on the performance of village fund management officials in Nisam Antara District.